Nonlinear State Estimation and Control for Chaos Suppression in MEMS Resonator - Angelo Marcelo Tusset; Átila Madureira Bueno; Claudinor Bitencourt Nascimento; Mauricio dos Santos Kaster; José Manoel Balthazar (Shock and Vibration)
During the last decade the chaotic behavior in MEMS resonators have been reported in a number of works. Here, the chaotic behavior of a micro-mechanical resonator is suppressed. The aim is to control the system forcing it to an orbit of the analytical solution obtained by the multiple scales method. The State Dependent Riccati Equation (SDRE) and the Optimal Linear Feedback Control (OLFC) strategies are used for controlling the trajectory of the system. Additionally, the SDRE technique is used in the state estimator design. The state estimation and the control techniques proved to be effective in controlling the trajectory of the system. Additionally, the robustness of the control strategies are tested considering parametric errors and measurement noise in the control loop.